Recognition of components affecting spatial healing in improving psychological outcomes in epidemic conditions - Fatemeh Mostafapoor; Fariborz Karimi (مهندسی و مدیریت ساخت, 2021)
Human societies today are facing an increasing rate of stress-related illnesses. Epidemic diseases are recognized worldwide as a major threat to physical and mental health, affecting people's daily behavior and causing devastating psychological effects such as anxiety, depression and fear on people's lives.Since the body of a space can play an important role in achieving peace and healing of the soul, today in architectural spaces, it is necessary to change the direction from mere functionalism to creating healing environments. On the other hand, this space should be such as to prevent the spread of the disease in these conditions among people or to be able to control it to a large extent; The purpose of this study is to identify these components affecting healing in a space, and then to provide solutions to create a healing space to improve psychological outcomes in epidemic conditions. According to studies, improvements in the design and use of different spaces to control the spread of infectious diseases can help reduce the effects of future outbreaks and epidemics in one space. The present research has been done by descriptive-analytical method, the information of which has been collected from a systematic search in sources related to the subject as well as reputable Internet databases and after screening documents and literature related to the subject. According to this method, the components and principles related to the subject have been briefly studied, analyzed and after achieving a comprehensive model in environmental healing, have led to the provision of solutions to create a healing atmosphere to improve psychological outcomes in epidemic conditions.